Multiexponential Analysis of the Water T2‐Relaxation in the Skeletal Muscle Provides Distinct Markers of Disease Activity Between Inflammatory and Dystrophic Myopathies - Araujo, Ericky C. A.; Marty, Benjamin; Carlier, Pierre G.; Baudin, Pierre‐Yves; Reyngoudt, Harmen (Journal of magnetic resonance imaging, 2021)
Background The monoexponential water T2 (T2‐mono) is a proven biomarker of disease activity in neuromuscular disorders (NMDs). However, it lacks specificity, being elevated in the presence of several pathological processes and pathomorphological alterations in the muscle tissue. Purpose To investigate the multiexponential behavior of the water T2‐relaxation in the skeletal muscle of NMD patients, aiming to identify more sensitive and specific biomarkers of disease activity. Study Type Retrospective case–control. Population Thirty Duchenne muscular dystrophy and 114 inclusion body myositis patients and 55 control subjects. Field Strength/Sequence 3T/Single‐voxel proton spectroscopy (1H‐MRS) and multispin‐echo (MSE) imaging. Assessment Water T2‐decay curves generated from 1H‐MRS data acquired at 14 echo‐times were fitted to mono‐ and biexponential models and the adjusted R2 of each fit was computed. Additionally, T2 spectra were generated from a regularized inverse Laplace transform. For comparison, water T2 maps were generated from the MSE data. The performances of the different variables at identifying patients were assessed via receiver operating characteristic (ROC)‐curve analysis. Statistical Tests Chi‐square, Kruskal–Wallis, and Mann–Whitney with Bonferroni correction for multiple comparisons. Results T2‐mono was elevated in patients (P<0.05), but could not distinguish inclusion body myositis (IBM) from Duchenne muscular dystrophy (DMD). While 79% of IBM data presented a biexponential behavior, this was only 16% and 10% for DMD and control data, respectively (P<0.05). All T2 spectra presented an intermediate‐T2 peak characterized by an elevated T2 in patients (P<0.05) and by a relative fraction that was abnormally smaller in IBM patients (P<0.05). Also, a long‐T2 peak was exclusively observed in IBM patients. A combination of T2‐spectrum variables performed best at identifying patients. Data Conclusion T2 spectra not only provided more sensitive and specific markers of disease presence than the T2‐mono, but also allowed distinguishing IBM from DMD patients. This must reflect distinct predominant pathological alterations between these diseases, suggesting that these markers provide additional pathophysiological/histopathological information that are missing from T2‐mono. Level of Evidence 3 Technical Efficacy Stage 3